1988
DOI: 10.1182/blood.v72.2.784.bloodjournal722784
|View full text |Cite
|
Sign up to set email alerts
|

Variable Philadelphia breakpoints and potential lineage restriction of bcr rearrangement in acute lymphoblastic leukemia

Abstract: Philadelphia (Ph1) chromosome breakpoints in acute lymphoblastic leukemia (ALL) are of two kinds: those within the breakpoint cluster region (bcr+), as in chronic myeloid leukemia (CML), and those outside it (bcr-). These encode different c-abl messenger RNAs (mRNAs), p210 and p190, respectively. It has been suggested that one class of Ph+ ALL (bcr+) may be a variant of CML arising in a multipotent stem cell, the other (bcr-) de novo ALL initiated in a lymphoid-committed progenitor. Thirty-two cases of ALL (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For Abelson disease in mice, infection of a committed lymphoid progenitor cell appears responsible for generating acute lymphoid leukemia (31). In human disease, some P210bcr/abl-positive acute lymphoid malignancies appear to be restricted to the lymphocyte lineage (32). Thus, the cases of acute lymphoid leukemia described here may have resulted from the infection of a cell committed to the lymphoid lineage.…”
Section: Several Of the Mice Displayed A Rumor Infiltration Of A Macrmentioning
confidence: 84%
“…For Abelson disease in mice, infection of a committed lymphoid progenitor cell appears responsible for generating acute lymphoid leukemia (31). In human disease, some P210bcr/abl-positive acute lymphoid malignancies appear to be restricted to the lymphocyte lineage (32). Thus, the cases of acute lymphoid leukemia described here may have resulted from the infection of a cell committed to the lymphoid lineage.…”
Section: Several Of the Mice Displayed A Rumor Infiltration Of A Macrmentioning
confidence: 84%
“…In Ph-positive ALL, about half of adult patients have traditional BCR intron 13 or 14 breakpoints on chromosome 22 generating the P210 form of BCR/ABL. Some of these patients have persistence of the Ph chromosome in remission and carry the Ph chromosome in myeloid cells and myeloid colonies grown in vitro, suggesting they represent cases of CML presenting in blast crisis after an unrecognized chronic phase (6)(7)(8)49). In contrast, the majority of ALL patients with the BCR intron 1 breakpoint characteristic of P190 BCR/ABL do not exhibit the additional cytogenetic abnormalities typical of CML blast crisis, lack the Ph chromosome in myeloid cells, and become Ph-negative during clinical remissions, suggesting they represent transformation of a cell type that is more limited in its differentiation potential (50).…”
Section: Discussionmentioning
confidence: 99%
“…The BCR‐ABL oncogene, which is the molecular counterpart of the Ph chromosome, is detected in two variant forms, either p190 or p210, by sensitive reverse‐transcription polymerase chain reaction (RT‐PCR) techniques. Studies on childhood Ph + ALL demonstrated that most carry p190 rather than p210 (Maurer et al , 1991; Suryanarayan et al , 1991) whereas, in adult patients with Ph + ALL, the p190 form is detected in 45–77% of patients (Schaefer‐Rego et al , 1988; Secker‐Walker et al , 1988; Kantarjian et al , 1991; Maurer et al , 1991; Mitterbauer et al , 1999; Gleißner et al , 2002). Although a large body of literature is available that documents the efficacy of BCR‐ABL detection in chronic myeloid leukaemia (CML) (Delage et al , 1991; Hughes et al , 1991; Lee et al , 1992; Roth et al , 1992; Cross et al , 1993), little information exists in Ph + ALL post BMT (Radich et al , 1997).…”
mentioning
confidence: 99%